In vitro evaluation of the antimicrobial activity of 70% ethanolic extract of piptadeniastrum africanum hook. F. (fabaceae) stem bark (World Journal of Current Medical and Pharmaceutical Research, 2024)
Introduction: Treatments for microbial infections are numerous, but for the most part unaffordable and increasingly ineffective. The aim of this study was to investigate the antimicrobial power of Piptadeniastrum africanum stem bark, a medicinal plant used to treat microbial infections in traditional settings. Methods: Phytochemical screening of the 70% ethanolic extract was carried out to identify the major groups of chemical molecules responsible for activity. The antimicrobial activity of the 70% ethanolic extract was then determined by evaluating and determining the sensitivity of nine clinical strains of bacteria and two fungi heavily involved in several types of infection. Results: Phytochemical screening revealed the presence of six groups of bioactive compounds in the 70% ethanolic extract (flavonoids, tannins, saponins, coumarins, polyphenols and alkaloids). Antifungal activity revealed the high sensitivity of Trichophyton mentagrophytes (MFC= 0.195 mg/mL; IC50= 0.2 mg/mL). The 70% ethanolic extract of Piptadeniastrum africanum was bactericidal against all clinical strains of Staphylococcus aureus. Conclusion: Piptadeniastrum africanum stem bark is a promising alternative for combating infectious diseases.